2021
DOI: 10.1038/s41467-021-22971-x
|View full text |Cite
|
Sign up to set email alerts
|

An RFC4/Notch1 signaling feedback loop promotes NSCLC metastasis and stemness

Abstract: Notch signaling represents a key mechanism mediating cancer metastasis and stemness. To understand how Notch signaling is overactivated to couple tumor metastasis and self-renewal in NSCLC cells, we performed the current study and showed that RFC4, a DNA replication factor amplified in more than 40% of NSCLC tissues, directly binds to the Notch1 intracellular domain (NICD1) to competitively abrogate CDK8/FBXW7-mediated degradation of NICD1. Moreover, RFC4 is a functional transcriptional target gene of Notch1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…The expression of FBXW7 shows a significant correlation with the treatment outcome of non-small cell lung cancer (NSCLC) [ 114 116 ]. Whole-exome sequencing and comprehensive immunoassays of early-stage lung squamous carcinoma reveals a significant decrease in FBXW7 expression levels, suggesting that FBXW7 may be one of the key factors influencing the progression of lung squamous carcinoma [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of FBXW7 shows a significant correlation with the treatment outcome of non-small cell lung cancer (NSCLC) [ 114 116 ]. Whole-exome sequencing and comprehensive immunoassays of early-stage lung squamous carcinoma reveals a significant decrease in FBXW7 expression levels, suggesting that FBXW7 may be one of the key factors influencing the progression of lung squamous carcinoma [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, NICD can translocate into the nucleus, where it allows for the attachment of the DNA-binding transcription factor, RBP-Jκ, resulting in the transcription of HES1, HES5, and HEY1, which subsequently suppresses differentiation. 34 Here, HDAC11 also caused the release of the intracellular domain of the Notch protein (NICD), which may have led to the formation of a HDAC11−NICD− RBP-Jκ ternary complex that stimulates transcription of key Notch targets for inhibiting myogenic differentiation. In addition, we demonstrated that overexpression of HDAC11 inhibited muscle regeneration using muscle-injured mice, and this may be related to the inhibition of MuSC myogenic differentiation by HDAC11.…”
Section: ■ Discussionmentioning
confidence: 99%
“…RFC4 is a known subunit of the replication factor C complex, which functions mainly in DNA replication [ 27 ]. Many reports have shown that RFC4 may play an important role in the proliferation, progression, invasion, and metastasis of cancer cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%